Durability Evaluation in Concrete Using Cracked Permeability and Chloride Permeability Tests. (18th August 2013) - Sounthararajan, V. M.; Sivakumar, A.
Abstract : The objective of this study is to identify the possibilities of utilizing the quarry dust in concrete to obtain an improved strength and durability properties of concrete. In the present study, the addition of quarry dust as alternative for natural sand has been investigated, and the durability properties of concrete were evaluated systematically by means of cracked water permeability and rapid chloride permeability tests. The permeability of concrete was assessed with initial stress applied to the concrete specimen and later checked for water permeability. Concrete mixes were casted using ordinary river sand and compared with 100% quarry dust substituted concrete. The addition of quarry dust significantly improved the concrete matrix properties in terms of strength and permeability resistance. The addition of fine quarry dust in concrete resulted in improved matrix densification compared to conventional concrete. Matrix densification has been studied qualitatively through petrographical examination using digital optical microscopy.